De nouvelles économies morales des mœurs ? Femmes, professionnels de santé et régimes discursifs en Tunisie - Ibtissem Ben Dridi; Irene Maffi (L’Année du Maghreb)
Drawing on two ethnographic researches conducted in Tunisia before and after the revolution of 2011, we intend to investigate how political, economic and social factors affected and still affect practices and discourses in the domain of sexual and reproductive health of state institutions, of the National Office of Family and Population, of health practitioners, feminist associations and ordinary women. We examine whether a new moral economy was created by different moral entrepreneurs or the alleged transformations brought about by the revolution elicited the public appearance of discourses and behaviours once silenced. We consider that local, national and transnational logics intertwine in the definition of a moral economy of “sexual freedom” imbued with religious discourses, social and family norms, the rhetoric of women’s and human rights and of biomedical rationality.